PENERAPAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB PADA SMK NURUL HUDA PRINGSEWU - Yuri Rahmanto; Debby Alita; Ade Dwi Putra; Permata Permata; Suaidah Suaidah (Universitas Teknokrat Indonesia, 2022)
Libraries have a very important role in increasing students' insight and knowledge. Usually, the library has its own room consisting of bookshelves that are neatly arranged based on the scientific group of books. SMK Nurul Huda Pringsewu is one of the schools that really pays attention to the convenience of students in adding insight, one of the efforts made by the school is the existence of a school library. The recording of borrowing and returning books at the library of SMK Nurul Huda Pringsewu is still recorded using books. This makes it difficult to properly monitor loan and repayment data, so that sometimes the loan process exceeds the time limit given. In addition, the recording of borrowing books which is still done conventionally also makes it difficult for librarian to monitor the availability of books that can be borrowed by students. Utilization of information systems in libraries is something that is indispensable to support the teaching and learning process in schools. Utilization of information systems can improve service quality, both speed and quality of information provided to manage or run library operations. In this service activity, the library information system of SMK Nurul Huda Pringsewu will be based on a website that can be accessed via a web browser so that it can be accessed anywhere and anytime.